Ticketing System: A Descriptive Research on the Use of Ticketing System for Project Management and Issue Tracking in IT Companies - Aglibar, Kent Darryl M.; Alegre, Garret Christopher T.; Del Mundo, Gerald I.; Duro, Kenny Francis O; Rodelas, Nelson C. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – IT companies are popular in the present time as technology arises in the entire world. Incidents and Requests for either clients or company internal are hard to manually track as it is a day-to-day transaction. To keep all the logs, IT Companies are using a ticketing system to track all the records they are gathering. One of the most popular ticketing systems is the JIRA. Either the support team or company internal is benefitting from the use of JIRA as it easily documents all the different transactions and keeps track of different incidents and requests. One of the cons of JIRA is its limited features. The researchers conducted research entitled “Ticketing System: A Descriptive Research on the Use of Ticketing System among Employees of ABC Company” where it aims to determine the effectiveness of JIRA as a ticketing system despite its limited features. Method – The researchers used a descriptive method to analyze the pros and cons of this ticketing system.  The researchers also mentioned how this system works to provide knowledge to the audience that is using other types of ticketing systems. Conclusion – It is concluded that this JIRA Ticketing system is helpful for both support groups and internal members of the company as they track all the incidents and request tickets for their clients despite JIRA's limited features. Recommendation – The researchers strongly recommend to venture out and try other analytic models and start with the ones mentioned in this study for a good foundation and idea. This is can provide the research a new set of results that can be useful to both established and startup companies. Practical Implication – This research will benefit not only the established companies but also the start up companies that are currently struggling in choosing an efficient ticketing system that work well not only in ticketing management but also in project management as well.